MEMILAH FAKTA DAN FIKSI DALAM KITAB SUCI: SEBUAH USAHA HERMENEUTIS - Rakhmat, Ioanes (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
Man in ancient times, adheres the ancient cosmology, who hold no separation between supranatural and natural realm, beliefs that every occurrences in the world is ruled under the Divine free determination and decree. There is no natural law runs out of the order and will of God (as defended by Deism). Therefore, for them, miracle is always a real experience and unseparable part of daily life. Miracle is not something irrational. On the contrary, ancient reason provides justifications for its occurency. Certainly, this conviction as a mythological interpretation that is being applied toward the facts which actually are ordinary and natural. Commonly, such mythological interpretations were generally proposed by the writers of holy books(scripture) long after the actual events, all of which, however was normal and natural. All miraculous stories in the holy books are entirely imaginary narratives which were codified post actum or post eventum, long after the unsensational actual events, and were built with religious apologetical or propagandistic purposes, rather than reporting the historical facts as they were. At their hand, the history is under religious-political apologies and propaganda.